Economic and social rights: demandable values in a democratic state (2003)
Departing of recognizing to the Economic, Social and Cultural Laws as values, the author indicates the imperious need to recognize the same ones like fundamental, but he thinks obstacles as the politics neoliberal that it he favours the market on the solidarity. Inventories are brought on the statistical results of the economic commanding politics in the world, which only has left. desolation and death and raises the need to lean movements antiglobalization as the defense of the rate Tobin to burden the speculative international capitals. Finally, it he insists on realizing a judgment for genocide against the ex-president Pastrana for the person in charge of the humanitarian crisis in Colombia, with more than thirty million poor and eight million wretches.